2020
DOI: 10.30973/aap/2020.6.0061003
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de los determinantes de la demanda de carne de pollo en el Centro-Este de México, 1996-2018

Abstract: El objetivo fue analizar los determinantes de la demanda de carne de pollo en la región Centro-Este de México, como los precios de las carnes de pollo, cerdo y bovino, ingreso y población; se probaron varios modelos econométricos. El modelo que tuvo el mejor ajuste, fue el de regresión lineal múltiple, ello conforme a las pruebas estadísticas, de la R-cuadrado ajustado, error estándar, t de Student, así como de las hipótesis económicas. El precio del producto fue inelástico (-0.18) sobre la demanda de pollo; e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The results showed that beer was an elastic good and that the variable that had the greatest effect on its demand was price. Rebollar et al (2020), estimated the demand for chicken meat in Mexico, for the period 1996-2018. In the same way, OLS was used in this research.…”
Section: Domestic Demand Estimationsmentioning
confidence: 99%
“…The results showed that beer was an elastic good and that the variable that had the greatest effect on its demand was price. Rebollar et al (2020), estimated the demand for chicken meat in Mexico, for the period 1996-2018. In the same way, OLS was used in this research.…”
Section: Domestic Demand Estimationsmentioning
confidence: 99%